Effect of prior female SARS-CoV-2 infection on IVF outcomes: a prospective cohort study - Huang, Jialyu; Liu, Yuxin; Xia, Leizhen; Zhao, Yan; Tian, Lifeng; Xu, Dingfei; Su, Qiong; Hu, Yina; Xie, Qiqi; Chen, Jia; Li, Yunjun; Ai, Xiaoyan; et al. (Frontiers in Endocrinology, 2023)
Introduction: The clinical impact of SARS-CoV-2 infection on human reproduction remains controversial. This prospective cohort study aimed to assess the effect of prior female SARS-CoV-2 infection on subsequent in vitro fertilization (IVF) outcomes. Materials and methods: A total of 451 women who underwent fresh IVF treatment between December 1, 2022 and April 30, 2023 were included from an academic fertility center. Participants were divided into the infected group if they had a prior COVID-19 history before cycle initiation (n = 252), while the control group were those uninfected (n = 199). The primary outcomes were the number of oocytes retrieved and clinical pregnancy rate after fresh embryo transfer. Multivariate linear and logistic regression analyses were conducted to control for potential confounders. Results: The number of oocytes retrieved (11.4±8.3 vs. 11.6±7.7; P = 0.457) and clinical pregnancy rate (70.3% vs. 73.7%; P = 0.590) were similar between infected and uninfected groups, with a fully adjusted β coefficient of 0 (95% confidence interval [CI]: -0.14–0.13) and odds ratio of 0.64 (95% CI: 0.20–2.07), respectively. Consistently, the two groups were comparable in cycle characteristics as well as other laboratory and pregnancy parameters. In both subgroup analyses and restricted cubic splines, different post-infection time intervals to IVF cycle initiation showed no significant associations with treatment outcomes. Conclusions: Prior SARS-CoV-2 infection in females had no adverse influence on subsequent IVF treatment, regardless of the time interval following infection. Our findings provide reassurance for infected women planning for assisted reproduction. Additional prospective cohort studies with larger datasets and longer follow-up are required to confirm the conclusion.